State management of public investment in road construction in Vietnam: Current situation and solutions - Dung, Nguyen Thi Tuyet; Toan, Nguyen Quoc (International Journal of Innovative Research and Scientific Studies, 2024)
This study examines Vietnam’s state management of public investment in road construction. The development of road transport infrastructure is in extremely high demand as Vietnam undergoes an economic transition. Despite the fact that the effects of the COVID-19 pandemic have caused the economy to grow more slowly recently, public investment in the transport industry has increased significantly. Several modern, large-scale road works that have been finished and put into operation are having a significant positive impact on urbanization, connecting regions, and socioeconomic development. However, public investment in road transport construction still has a lot of issues that need to be fixed. The state’s weakness is one of the primary issues that reduces investment efficiency. This study analyzes the state management of public investment in road construction, according to the following contents: legal system and policies; formulation and implementation of public investment plans; inspection and supervision by state management agencies. The method of collecting secondary data and primary data (through sociological investigation) is used and combined with Statistical Package for the Social Sciences (SPSS) software to determine the influencing factors and find out the problems and their causes. Therefore, this study proposes a number of urgent and practical solutions to improve the state management of public investment in road construction and develop a synchronized road transport network.